In vitro breast cancer models for studying mechanisms of resistance to endocrine therapy - Gary J. Cheng; Euphemia Y. Leung; Dean C. Singleton (Open Exploration Publishing Inc., 2022)
The development of endocrine resistance is a common reason for the failure of endocrine therapies in hormone receptor-positive breast cancer. This review provides an overview of the different types of in vitro models that have been developed as tools for studying endocrine resistance. In vitro models include cell lines that have been rendered endocrine-resistant by ex vivo treatment; cell lines with de novo resistance mechanisms, including genetic alterations; three-dimensional (3D) spheroid, co-culture, and mammosphere techniques; and patient-derived organoid models. In each case, the key discoveries, different analysis strategies that are suitable, and strengths and weaknesses are discussed. Certain recently developed methodologies that can be used to further characterize the biological changes involved in endocrine resistance are then emphasized, along with a commentary on the types of research outcomes that using these techniques can support. Finally, a discussion anticipates how these recent developments will shape future trends in the field. We hope this overview will serve as a useful resource for investigators that are interested in understanding and testing hypotheses related to mechanisms of endocrine therapy resistance.